2013
DOI: 10.1371/journal.pone.0054563
|View full text |Cite
|
Sign up to set email alerts
|

Nischarin Is Differentially Expressed in Rat Brain and Regulates Neuronal Migration

Abstract: Nischarin is a protein known to inhibit breast cancer cell motility by regulating the signaling of the Rho GTPase family. However, little is known about its location and function in the nervous system. The aim of the present study was to investigate the regional and cellular expression and functions of Nischarin in the adult rodent brain. As assessed by real-time PCR, Western blot analysis and immunostaining, we found that Nischarin was widely distributed throughout the brain, with a higher expression in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 27 publications
(36 reference statements)
2
21
0
Order By: Relevance
“…This hypothesis was also based on previous findings that linked Nischarin to decreasing the function of key cell attachment proteins, such as FAK (1,42). Also, it has been shown by other investigators that Nischarin regulates apoptosis and metastasis of breast cancer (43), loss of Nischarin promotes cell proliferation metastasis of ovarian cancer (42), and suppression of Nischarin promotes neuronal migration (44), suggesting that Nischarin has significant role in other cancers as well. We found that Nischarin-reduced cells had increased proliferation regardless of the substrate they were seeded on.…”
Section: Discussionmentioning
confidence: 72%
“…This hypothesis was also based on previous findings that linked Nischarin to decreasing the function of key cell attachment proteins, such as FAK (1,42). Also, it has been shown by other investigators that Nischarin regulates apoptosis and metastasis of breast cancer (43), loss of Nischarin promotes cell proliferation metastasis of ovarian cancer (42), and suppression of Nischarin promotes neuronal migration (44), suggesting that Nischarin has significant role in other cancers as well. We found that Nischarin-reduced cells had increased proliferation regardless of the substrate they were seeded on.…”
Section: Discussionmentioning
confidence: 72%
“…Nischarin is highly expressed on the leading edge of neurons (31). Silencing of Nischarin in both rat and mouse neurons has been found to increase neuronal migration (31).…”
Section: Nischarin In the Brainmentioning
confidence: 99%
“…Silencing of Nischarin in both rat and mouse neurons has been found to increase neuronal migration (31). Nischarin is expressed by mature neurons to prevent them from further migration (31). Neuronal migration is necessary in the embryonic period for normal brain formation (31).…”
Section: Nischarin In the Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Nischarin mRNA expression levels have been reported to be significantly higher in the brain and kidney compared with those in the heart, liver, lung and skeletal muscle ( 19 ). Additionally, Nischarin expression was recently revealed to be widely distributed in rat brain tissue, particularly in the cerebral cortex and hippocampus, and is hypothesized to exhibit a significant role in neuronal migration ( 25 ).…”
Section: Introductionmentioning
confidence: 99%